CARA DAN MANFAAT PENGGUNAAN MEDIA PEMBELAJARAN DI KELAS - I Made Puspe (Fakultas Dharma Duta, 2018)
Education process changes through perfection process which is done by stakeholders every certain decade. This is a concrete effort from government in order to give education service for people maximally. Why is it so? Improving quality of education at school should be in line with technology improvement which is getting sophisticated that provides both old and latest knowledge. Learning knowledge in class needs to use series of media tools of technology that makes work more effective and efficient. Using learning media as a learning support will be effective if the teacher has a creativity to use the appropriate learning method. Using learning media in class is useful for students to create fun, interesting and exciting learning therefore the students can actively study better. Learning media can represent what teacher feels less says through certain words or sentences. Even the absurdity of material can be completed by the existence of learning media. Therefore creating fun learning and omitting unpleasant process can improve learning motivation of student in class.